Identification of Coral Reef Conditions Using Hydro-Acoustic Technology in Giligenting Island, Sumenep Regency Indonesia - Fauzan Syaikhu Islam; Danar Guruh Pratomo; Khomsin Khomsin (IPTEK Journal of Proceedings Series, 2019)
Coral reefs are one of the major ecosystems in the coastal region with high biodiversity and resource level. As productive ecosystems with high economic and ecological potential, the existence of coral reef ecosystems must be sustainably managed. One of the areas with high diversity of coral reefs is Giligenting Island located in Sumenep regency. This research was conducted by taking primary data in the form of tidal data, bathymetry data and Side Scan Sonar recordings. From the primary data and then processed until produces 3 dimensional model of seabed features that are then interpreted and analyzed to obtain information about healthy or damaged coral reefs, using underwater geo-tagged photos to validate. The 3-dimensional model has a maximum depth of 7.667 meters and 1.403 meters at minimum depth with an area of 100,536.097 m2. From the interpretation of Side Scan Sonar acoustic images it is found the area of sand feature is 30.79%; the area of mud feature equal to 29.94%; the healthy coral covering 35.75% of the survey area, consisting 10.09% of coral reef barrier reef feature, and 25.66% of small coral reef feature; and 3.52% of damaged coral reef feature from total 43,527.110 m2 Side Scan Sonar survey area.